2014
DOI: 10.1186/1471-2180-14-116
|View full text |Cite
|
Sign up to set email alerts
|

The effects of chemical interactions and culture history on the colonization of structured habitats by competing bacterial populations

Abstract: BackgroundBacterial habitats, such as soil and the gut, are structured at the micrometer scale. Important aspects of microbial life in such spatial ecosystems are migration and colonization. Here we explore the colonization of a structured ecosystem by two neutrally labeled strains of Escherichia coli. Using time-lapse microscopy we studied the colonization of one-dimensional arrays of habitat patches linked by connectors, which were invaded by the two E. coli strains from opposite sides.ResultsThe two strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 49 publications
(62 reference statements)
1
27
0
Order By: Relevance
“…In the absence of external mixing (which occurs in shaken flasks), dispersal, chemotaxis, and aggregation become key drivers of bacterial community dynamics. As a result of these factors, the population expansion of bacteria that colonize a structured habitat does not obey the statistics of an ideal gas; instead, high-density demographic clusters form in close proximity to unoccupied territory (7,(85)(86)(87)(88). Keymer et al demonstrated that these processes allow E. coli to organize into a structured metapopulation (a population of populations) when colonizing an array of coupled habitat patches (7).…”
Section: Building Up Bacterial Communitiesmentioning
confidence: 97%
See 1 more Smart Citation
“…In the absence of external mixing (which occurs in shaken flasks), dispersal, chemotaxis, and aggregation become key drivers of bacterial community dynamics. As a result of these factors, the population expansion of bacteria that colonize a structured habitat does not obey the statistics of an ideal gas; instead, high-density demographic clusters form in close proximity to unoccupied territory (7,(85)(86)(87)(88). Keymer et al demonstrated that these processes allow E. coli to organize into a structured metapopulation (a population of populations) when colonizing an array of coupled habitat patches (7).…”
Section: Building Up Bacterial Communitiesmentioning
confidence: 97%
“…Approaches that allow several species to collectively define the chemical complexity of the medium while retaining the contributing cells in pure culture could, for instance, be implemented by using the on-chip ecosystems or 3D-printing technique described above. Other techniques that establish the physical segregation of populations while allowing chemical interactions rely on coupling separate culturing wells through a porous membrane (8) or hydrogel (108) or use shallow slits that prevent cellular migration from one compartment to the other (87,109). We expect that these and other (110) approaches will prove to be valuable tools to unravel the complexity of natural bacterial communities.…”
Section: Breaking Down Bacterial Communitiesmentioning
confidence: 97%
“…; Van Vliet et al . ). A challenge to confining bacteria to liquid‐saturated paper is the liquid film that forms when wet paper comes in contact with a surface (e.g.…”
Section: Resultsmentioning
confidence: 97%
“…As both landscapes are colonised from the same inoculation zone, and thus by the same initial community, the effect of branching on the range expansions can be assessed by comparing the community composition at the extremities of both landscapes. Paper scaffolds were saturated with rich growth medium (LB) and inoculated in the centre with a 1:1 mixture of neutrally labelled E. coli, isogenic except for a green fluorescent protein (GFP) versus red fluorescent protein (RFP) insertion in the Lac operon (Keymer et al 2008;Hol et al 2013;Van Vliet et al 2014). A challenge to confining bacteria to liquid-saturated paper is the liquid film that forms when wet paper comes in contact with a surface (e.g.…”
Section: Case Study 1: Dendritic Network Connectivitymentioning
confidence: 99%
“…During phase (i), the majority of E. coli bacteria are planktonic, motile, and migrate between patches rapidly, whereas in phase (ii), the majority of E. coli become sessile and show an increase in surface-associated growth [16]. Without predator (figure 1b,c), one observes phases (i) and (ii) only (see [38] for a detailed analysis of the colonization process). When prey and predator are both (simultaneously) inoculated, predation starts to dominate in phases (ii) and (iii) and the population density of E. coli starts to decline approximately 10-20 h after inoculation.…”
Section: Resultsmentioning
confidence: 99%